2017
DOI: 10.18553/jmcp.2017.23.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adherence and Persistence with Oral Bisphosphonate Therapy in an Integrated Health Care Delivery System

Abstract: Background Examining drug exposure is essential to pharmacovigilance, especially for bisphosphonate (BP) therapy. Objective This study examines differences in four measures of oral BP exposure: treatment discontinuation, adherence, persistence, and non-persistence. Methods Among women aged ≥50 years who initiated oral BP therapy during 2002–2007 with at least three years of health plan membership follow-up, discontinuation was defined by evidence of no further treatment during the study observation period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Using the days' supply of dispensed drug (excluding prescription overlap > 30 days), with adherence calculated using the proportion of days covered, 6 we identified those continuing adherent BP treatment for at least 3 and 5 years, defined by adherence ≥ 60% each year as well as BP treatment within the 60 days prior to the end of the treatment period. Continuation rates were examined by year of BP initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Using the days' supply of dispensed drug (excluding prescription overlap > 30 days), with adherence calculated using the proportion of days covered, 6 we identified those continuing adherent BP treatment for at least 3 and 5 years, defined by adherence ≥ 60% each year as well as BP treatment within the 60 days prior to the end of the treatment period. Continuation rates were examined by year of BP initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Bisphosphonate exposure was determined based on dispensing dates and days’ supply of each prescription. Stockpiling was allowed for prescriptions that overlapped 30 days or less; the second prescription took precedence when prescriptions overlapped for more than 30 days [ 13 ]. Each patient’s BP use was updated at each successive quarter (90-day interval) of follow-up after the index date.…”
Section: Methodsmentioning
confidence: 99%
“…Ongoing BP exposure (including all second-generation oral bisphosphonate drugs) was determined using the days supply of dispensed drugs, where prescription/refill gaps of 1 or 2 days were bridged, and stockpiling for prescriptions that overlapped for less than 30 days was allowed. 5 We considered each quarter of follow-up as being on (adherent) treatment if a woman had evidence of a PDC that was 0.6 or greater. 6…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…In previous studies, we examined treatment adherence for the first 3 years following BP initiation and have also shown that an adherence criteria of 0.6 (based on the proportion of days covered [PDC] by the dispensed days supply of BP) provides a practical approach for characterizing continued adherence in real-world clinical settings. 5,6 In the current study, we examined the association of demographic and clinical factors with BP continuation after the first 5 years of treatment. We also examined whether treatment continuation was determined by the era in which BP treatment was prescribed.…”
mentioning
confidence: 99%